Insulin-like growth factor 1 and growth seasonality in reindeer (Rangifer tarandus) - comparisons with temperate and tropical cervids - Suttie, J. M.; White, R. G.; Manley, T. R.; Breier, B. H.; Gluckman, P. D.; Fennessy, P. F.; Woodford, K. (Rangifer, 1993)
Growth in temperate and arctic deer is seasonal, with higher growth rates in spring and summer while growth rates are low or negative in autumn and winter. We have measured IGF1 concentrations in the plasma of reindeer calves exposed to a manipulated photoperiod, indoors, of either 16 hours light followed by 8 hours dark each day (16L:8D) (n = 3) or 8L:16D (n = 3) from about the autumnal to the vernal equinox, to determine whether the seasonal growth spurt normally seen in spring is associated with changes in the circulating level of IGF1. A high quality concentrate diet was available ad libitum. The animals were weighed, and bled every 2 weeks and plasma samples assayed for IGF1 by radioimmunoassay. 6-8 weeks after the start of the study those calves exposed to 16L.-8D showed a significant increase in plasma IGF1 concentration which was maintained until the close of the experiment, 24 weeks after the start. In contrast IGF1 plasma concentrations in those calves exposed to a daylength of 8L:16D did not significantly alter during the study. The elevated IFG1 in the 16L:8D group was associated with rapid weight gain compared with the 8L:16D group. We have shown that the seasonal growth spurt is preceded by an elevation in plasma IFG1 concentration. Further, this elevation in IGF1 is daylength dependent. For comparison IGF1 and growth rate seasonal profiles from temperate and tropical deer are included. This comparison reveals that seasonal increases in IGF1 take place only in animals with a seasonal growth spurt. Thus IGF1 plasma level elevations seem most closely associated with the resumption of rapid growth in spring following the winter.